Electronic properties and optical behaviors of bulk and monolayer ZrS2: A theoretical investigation. (January 2019) - Vu, Tuan V.; Lavrentyev, A.A.; Thuan, Doan V.; Nguyen, Chuong V.; Khyzhun, O.Y.; Gabrelian, B.V.; Tran, Khanh C.; Luong, Hai L.; Tung, Pham D.; Pham, Khang D.; Dang, Phuc Toan; Vo, Dat D.
Abstract: In this paper, we study the difference in electronic and optical properties of bulk and monolayer zirconium sulfide by applying the APW + lo method in the framework of density functional theory. All calculation is performed at the energy level of visual light and higher ranging from 0 eV to 15 eV. Our results demonstrates that except for the underestimated band gap like other GGA calculation, the remain properties like dielectric function, the reflectivity, absorption and loss energy are close to experiment. The valence band is constructed by mainly sulfur s / p -states and the lower portion of zirconium s / p / d -states. The conduction band is mostly donated by zirconium d -state. In contrast with bulk structure, the valence band maximum in monolayer has the triple peak at Γ point, making its monolayer be more sensitive to light absorption. The dielectric function has the highest peak at about 1.5–2.5 eV with remarkable anisotropy, beyond this level to the ultraviolet region the anisotropy decreases and almost disappears at energy larger than 10 eV. The absorption is at 106 x 10 4 cm -1 for energy range 5–10 eV, while the reflectivity is at its highest value of 30 %–50 % in the energy range from 0 to 8 eV. The energy loss of monolayer is higher than those of bulk. For optical and electronic properties, the monolayer show sharper peaks and their clear separation indicate the progressive application of monolayer zirconium sulfide. Highlight: Monolayer ZrS2 has new interband transitions at energy levels of 4-7 eV and 7-10 eV. For energy ranging from -14 eV to 6 eV, the dielectric constants, energy loss, and reflectance are close to experimental values. ZrS2 is highly anisotropic to the parallel and perpendicular components of electric field at energy lower than 10 eV. The energy loss L (ω) in monolayer is higher than in bulk. Our results give an explanation on perspective optical properties of monolayer ZrS2, which can be helpful for further design and application of this material.